2020
DOI: 10.1186/s40104-020-00444-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fiber and threonine content on intestinal barrier function in pigs challenged with either systemic E. coli lipopolysaccharide or enteric Salmonella Typhimurium

Abstract: Background: The independent and interactive effects of dietary fiber (DF) and threonine (Thr) were investigated in growing pigs challenged with either systemic E. coli lipopolysaccharide (LPS) or enteric Salmonella Typhimurium (ST) to characterise their effect on intestinal barrier function. Results: In experiment 1, intestinal barrier function was assessed via oral lactulose and mannitol (L:M) gavage and fecal mucin analysis in pigs challenged with E. coli LPS and fed low fiber (LF) or high fiber (HF) diets w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 66 publications
5
12
0
Order By: Relevance
“…Previous studies have reported a reduced efficiency of utilizing dietary Thr for PD with increasing DF content, thereby increasing the dietary Thr requirement growth [2,8,9]. This effect is largely attributed to increased endogenous protein/AA losses [7,13,32]. In the present study, we observed that the HF diet reduced ATTD of N, which is consistent with reports from previous studies [2,8], but no significant effect of fCP was observed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have reported a reduced efficiency of utilizing dietary Thr for PD with increasing DF content, thereby increasing the dietary Thr requirement growth [2,8,9]. This effect is largely attributed to increased endogenous protein/AA losses [7,13,32]. In the present study, we observed that the HF diet reduced ATTD of N, which is consistent with reports from previous studies [2,8], but no significant effect of fCP was observed.…”
Section: Discussionsupporting
confidence: 92%
“…Gene expression analysis showed significant treatment effects on target genes only in the colon. In the colonic tissue, feeding the HfCP diet reduced the expression of MUC2 gene, with no effect on MUC5ac, while feeding high DF increased the expression of both MUC2 and MUC5ac genes, which agrees with previous reports [14,31,32]. Expression of MUC2 was previously shown to be correlated with mucin secretion [31] which increases Thr requirements for protein deposition [2].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, many recent studies have focused on the influence of the relationship between dietary Thr and dietary fiber on intestinal barrier function [ 85 , 86 , 87 ]. Dietary fiber has positive effects on barrier function by boosting mucus secretion and mucin synthesis [ 88 ].…”
Section: The Roles Of Thr On Intestinal Health and Functionsmentioning
confidence: 99%
“…Dietary fiber has positive effects on barrier function by boosting mucus secretion and mucin synthesis [ 88 ]. However, high dietary fiber increases the loss of endogenous amino acids, resulting in a greater need for Thr to maintain mucin production [ 85 , 89 ]. The effect of Thr on intestinal barrier protein is influenced by the amount of fiber in the diet.…”
Section: The Roles Of Thr On Intestinal Health and Functionsmentioning
confidence: 99%
“…Several factors, including dietary protein and fiber levels, could influence ileal EAA losses in non-ruminant animals [ 1 , 4 ]. Dietary fiber contributes to an increase in EAA losses because of its effects on mucous secretion and cell proliferation [ 6 ]. In order to obtain consistent and reliable EAA losses data for standardization of apparent ileal amino acid digestibility values, it is important to evaluate the effect of different dietary components, such as fiber type (soluble vs. non-soluble) and viscosity, of feed ingredients on basal ileal EAA flow.…”
Section: Introductionmentioning
confidence: 99%